SADI-S and SG surgeries induce distinct bile acid profiles linked to improved glucose metabolism via microbiota interactions - Ma, Subo; Zhang, Zheng; Wei, Zhiqiang; Hu, Lifu; Wang, Lun; Shen, Zhubin; Fang, Chaonv; Jiang, Tao (Frontiers in Microbiology, 2025)
IntroductionAlthough bariatric surgery profoundly ameliorates type 2 diabetes (T2D), the mechanisms whereby specific procedures confer metabolic benefits through bile acid (BA) remodeling remain incompletely defined. This study compared the effects of single-anastomosis duodenal-ileal bypass with sleeve gastrectomy (SADI-S) and sleeve gastrectomy (SG) on BA profiles and their association with metabolic outcomes in a rodent model of T2D.MethodsMale Wistar rats with T2D underwent SADI-S, SG, or sham operation. Metabolic parameters, including fasting blood glucose, HbA1c, glucagon-like peptide-1 levels, triglycerides, gut microbiota composition, and comprehensive serum/fecal BA profiles, were assessed 5 weeks post-surgery. Statistical analyses included t-tests and Pearson correlations, with false discovery rate correction applied.ResultsBoth SADI-S and SG significantly ameliorated hyperglycemia, dyslipidemia, and β-cell integrity compared to sham operation, with SADI-S demonstrating superior efficacy. SADI-S induced a more pronounced elevation of portal serum BAs (34 vs. 25 species in SG), including key regulators such as chenodeoxycholic acid and lithocholic acid. Critically, multiple elevated serum BAs (e.g., chenodeoxycholic acid, lithocholic acid, glycoursodeoxycholic acid) exhibited strong negative correlations with fasting blood glucose, HbA1c, and triglycerides, while positively correlating with glucagon-like peptide-1 levels. Shifts in gut microbiota correlated with specific BA changes, supporting a ‘microbiota-BA-metabolism’ axis.ConclusionSADI-S and SG induce distinct, surgery-specific BA remodeling that is significantly associated with metabolic improvements in T2D. The robust correlations between specific BA species and metabolic parameters underscore their potential as mediators and therapeutic targets. SADI-S promotes a more extensive and beneficial BA profile, aligning with its superior metabolic efficacy.